PEM fuel cell performance improvement through numerical optimization of the parameters of the porous layers. (13th March 2020) - Carcadea, Elena; Varlam, Mihai; Ismail, Mohammed; Ingham, Derek Binns; Marinoiu, Adriana; Raceanu, Mircea; Jianu, Catalin; Patularu, Laurentiu; Ion-Ebrasu, Daniela
Abstract: A numerical model for a PEM fuel cell has been developed and used to investigate the effect of some of the key parameters of the porous layers of the fuel cell (GDL and MPL) on its performance. The model is comprehensive as it is three-dimensional, multiphase and non-isothermal and it has been well-validated with the experimental data of a 5 cm 2 active area-fuel cell with/without MPLs. As a result of the reduced mass transport resistance of the gaseous and liquid flow, a better performance was achieved when he GDL thickness was decreased. For the same reason, the fuel cell was shown to be significantly improved with increasing the GDL porosity by a factor of 2 and the consumption of oxygen doubled when increasing the porosity from 0.40 to 0.78. Compared to the conventional constant-porosity GDL, the graded-porosity (gradually decreasing from the flow channel to the catalyst layer) GDL was found to enhance the fuel cell performance and this is due to the better liquid water rejection. The incorporation of a realistic value for the contact resistance between the GDL and the bipolar plate slightly decreases the performance of the fuel cell. Also the results show that the addition of the MPL to the GDL is crucially important as it assists in the humidifying of the electrolyte membrane, thus improving the overall performance of the fuel cell. Finally, realistically increasing the MPL contact angle has led to a positive influence on the fuel cell performance. Graphical abstract: Image 1 Highlights: A well-validated comprehensive 3D model for a PEM fuel cell has been created. Effects of porous layers parameters are investigated. Fuel cell performance significantly improves with increasing GDL porosity. Graded-porosity GDL improves fuel cell performance. MPL assists in humidifying membrane electrolyte and improves overall performance.